The Health Implications of Social Pensions: Evidence from China's New Rural Pension Scheme - Lingguo Cheng; Hong Liu; Ye Zhang; Zhong Zhao (Institute for the Study of Labor (IZA), 2016)
This paper estimates the causal effect of income on health outcomes of the elderly and investigates underlying mechanisms by exploiting an income change induced by the launch of China's New Rural Pension scheme (NRPS). Using this policy experiment, we address the endogeneity of pension income by applying a fixed-effect model with instrumental variable correction. The results reveal that pension enrollment and income from the NRPS both have had a beneficial impact on objective measures of physical health, cognitive function, and psychological well-being of the rural elderly, and also reduced mortality over a three-year horizon by 6 percentage points. Evidence further suggests that pension recipients respond to the new pension income in multiple ways: improved nutrition intake, better accessibility to health care, increased informal care, increased leisure activities, and better self-perceived relative economic situation. These in turn act as channels from pension income to health of the Chinese rural elderly.
Keywords: H55; I12; I38; J14; 330; pension income; health; channels; elderly; China